Legitimacy of Smart Contracts from the Perspective of Islamic Law: A Case Study of Blockchain Transactions - Atiyah, Ghassan Adhab; Manap, Nazura Abdul; Ibrahim, Ahmed Ismael; Rahman, Abdur (Institut Agama Islam Negeri Curup, 2024)
Blockchain smart contracts is a digital program based on the blockchain design that accommodates certain data stored in their internal logic. The decentralized nature of this technology prevents unauthorized access. This technology require the use of cryptocurrencies to be effectively utilized as a medium of exchange. While cryptocurrencies have received wide recognition as an improvement to modern business transactions. However, in the Muslim communities, Muslim scholars have divergent views on the permissibility and prohibition of cryptocurrencies on certain grounds. Islamic law is characterized by outstanding flexibility that enables it to keep pace with the development of time and place, and gives it the validity to interact to address emerging issues that stand in people's way. This study aims to examine blockhain smart contracts, how they work, the religious ruling surrounding its permissibility. As well as the consensus of Muslim Scholars on its usage by Muslim communities. The study adopts qualitative doctrinal, library based or normative judicial research to analyze blockchain smart contracts and their suitability and compatibility with Islamic law. By examining the law from the perspective of social reality, the researchers qualitatively analyzed the concept of Smart contracts within the boundaries of law and its application under Islamic law. Delving into deductive reasoning and conclusions based on consensus of scholars. This study found that blockchain smart contracts falls within the permissibility principle, The Maliki school sale on credit and negotiations under the ijtihadi perspective. This research suggests the need for further study to shed light on this new type of contract to support its acceptability among Muslim communities.